2011
DOI: 10.1002/yea.1906
|View full text |Cite
|
Sign up to set email alerts
|

Glucose signalling pathway controls the programmed ribosomal frameshift efficiency in retroviral‐like element Ty3 in Saccharomyces cerevisiae

Abstract: Ty3 elements of S. cerevisiae contain two overlapping coding regions, GAG3 and POL3, which are functional homologues of retroviral gag and pol genes, respectively. Pol3 is translated as a Gag3-Pol3 fusion protein dependent on a +1 programmed frameshift at a site with the overlap between the two genes. We show that the Ty3 frameshift frequency varies up to 10-fold in S. cerevisiae cells depending on carbon source. Frameshift efficiency is significantly lower in cells growing on glucose as carbon source than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Its frameshifting is not a constitutive process but is regulated over a 10-fold response window depending on carbon source. The glucose-signaling pathway involved has been investigated in depth ( 216 ).…”
Section: Occurrence and Function In Mobile Elements Derivatives And mentioning
confidence: 99%
“…Its frameshifting is not a constitutive process but is regulated over a 10-fold response window depending on carbon source. The glucose-signaling pathway involved has been investigated in depth ( 216 ).…”
Section: Occurrence and Function In Mobile Elements Derivatives And mentioning
confidence: 99%
“…Frameshift occurs at +1 direction without tRNA slippage by out-of-frame binding of valyl-tRNA to the GUU codon at the A-site of the ribosome [28]. Previously, it was reported that the frameshift frequency in Ty3 can be modulated by growth conditions [9]. It is activated by nonfermentable carbon sources up to 3-fold in a Snf1p dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The PRF rate in Ty3 is activated more than 3-fold in the yeast cells that are grown in low glucose medium in a Snf1p dependent manner. cAMP dependent protein kinase-A is also involved in the regulation of frameshift efficiency in Ty3 [9]. In addition, we have analyzed the effects of glucose signaling on the PRF efficiency in Ty1 elements and shown that the Ty1 type +1 PRF frequency decreases several fold in glycerol-lactate-grown S. cerevisiae cells [8].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations